2015
DOI: 10.2214/ajr.15.14341
|View full text |Cite
|
Sign up to set email alerts
|

JOURNAL CLUB: Distinguishing Osteomyelitis From Ewing Sarcoma on Radiography and MRI

Abstract: OBJECTIVE The purpose of this study was to determine whether clinical and imaging features can distinguish osteomyelitis from Ewing sarcoma (EWS) and to assess the accuracy of percutaneous biopsy versus open biopsy in the diagnosis of these diseases. MATERIALS AND METHODS Three radiologists reviewed the radiographs and MRI examinations of 32 subjects with osteomyelitis and 31 subjects with EWS to determine the presence of 36 imaging parameters. Information on demographic characteristics, history, physical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 31 publications
3
66
0
6
Order By: Relevance
“…In some ES cases of the jaws, distinction from chronic osteomyelitis (OM) can be challenging on the basis of clinical findings (demographics, history, physical examination, and laboratory findings) and on the basis of cross-sectional imaging features. As recently suggested, other than ethnicity (African Americans are more likely to have OM than ES), no clinical feature improves diagnostic accuracy while among the morphologic features (without DWI), only the presence of a soft tissue mass at MRI appears to be significantly associated with ES [50]. On FDG PET CT, both OM and ES show increased tracer uptake within the bone and within the surrounding soft tissues due to increased glucose metabolism in inflammatory and malignant tissue, respectively.
Fig.
…”
Section: Primary Intraosseous Tumorsmentioning
confidence: 99%
“…In some ES cases of the jaws, distinction from chronic osteomyelitis (OM) can be challenging on the basis of clinical findings (demographics, history, physical examination, and laboratory findings) and on the basis of cross-sectional imaging features. As recently suggested, other than ethnicity (African Americans are more likely to have OM than ES), no clinical feature improves diagnostic accuracy while among the morphologic features (without DWI), only the presence of a soft tissue mass at MRI appears to be significantly associated with ES [50]. On FDG PET CT, both OM and ES show increased tracer uptake within the bone and within the surrounding soft tissues due to increased glucose metabolism in inflammatory and malignant tissue, respectively.
Fig.
…”
Section: Primary Intraosseous Tumorsmentioning
confidence: 99%
“…Lamellar periosteal reaction was seen in 13 subjects with Ewing's sarcoma and five with osteomyelitis, spiculated periosteal reaction was seen in five subjects with Ewing's sarcoma and one with osteomyelitis, and a serpiginous medullary or cortical tract (i.e., a longitudinally oriented tortuous medullary or cortical lucency seen on radiographs or signal abnormality seen on MR images traversing the medulla and cortex) was seen in none of the subjects with Ewing's sarcoma and in four subjects with osteomyelitis. 19 McCarville reported that nonpredictive MRI parameters included cortical thinning (in 17 subjects with Ewing's sarcoma and seven subjects with osteomyelitis) (p = 0.08), spiculated periosteal reaction (in five subjects with Ewing's sarcoma and in none of the subjects with osteomyelitis) (p = 0.06), and a cavity in bone (in one subject with Ewing's sarcoma and three subjects with osteomyelitis) (p = 0 .33). Two of the three cavities in bone in patients with osteomyelitis (67%) showed the penumbra sign (a peripheral hyperintense layer on unenhanced T1-weighted images that shows intense enhancement on contrast-enhanced images).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the three cavities in bone in patients with osteomyelitis (67%) showed the penumbra sign (a peripheral hyperintense layer on unenhanced T1-weighted images that shows intense enhancement on contrast-enhanced images). 19 Plain film findings of osteomyelitis lag the onset of infection by days to weeks. Initial findings may include only subtle soft tissue edema near the involved metaphysis.…”
Section: Discussionmentioning
confidence: 99%
“…The main differential diagnoses consist of osteolytic osteosarcoma and small-cell osteosarcoma in children and adolescents, osteomyelitis in all age groups, and non-Hodgkin's lymphoma in adulthood. 12 In children, unifocal Langerhans cell histiocytosis is another differential, but the periosteal reaction is often less aggressive, and an eosinophilic granuloma may have a sequestrum. In the spine, ES may mimic spondylitis because of its high signal intensity in T2-weighted images, 4,13 whereas in the rare case of sacroiliac joint involvement, it should be distinguished from septic sacroiliitis (►Fig.…”
Section: Differential Diagnosismentioning
confidence: 99%